2013
DOI: 10.2135/cropsci2012.06.0385
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability for Total Phenols and Secondary Traits in a Diverse Set of Colored (Red, Blue, and Purple) Maize

Abstract: Maize (Zea mays L.) genetic diversity includes an array of kernel colors (red, blue, and purple), which are minimally used specialty corns when compared to yellow and white types commonly grown. Plant pigments are antioxidant phytochemicals produced as secondary metabolites. Antioxidants have been linked to various anticancer and other anti‐inflammatory health benefits. Alternate colors have been the subject of little breeding research, including the potential for high grain yield and high phenolic content fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…Furthermore, a similar anthocyanin profile was also found in corn leaves, cobs and husks (Fossen, Slimestad, & Andersen, 2001;Li et al, 2008;Zhao et al, 2008). Although data on the anthocyanins and antioxidant activity of purple corn are available, these parameters have not yet been examined in waxy corn (Mahan, Murray, Rooney, & Crosby, 2013). Hence, the anthocyanins found in coloured waxy corn were determined for the first time in this study.…”
Section: Introductionsupporting
confidence: 52%
“…Furthermore, a similar anthocyanin profile was also found in corn leaves, cobs and husks (Fossen, Slimestad, & Andersen, 2001;Li et al, 2008;Zhao et al, 2008). Although data on the anthocyanins and antioxidant activity of purple corn are available, these parameters have not yet been examined in waxy corn (Mahan, Murray, Rooney, & Crosby, 2013). Hence, the anthocyanins found in coloured waxy corn were determined for the first time in this study.…”
Section: Introductionsupporting
confidence: 52%
“…Direct comparison of studies in waxy corn is not available. However, genotype was more important source of variations in anthocyanin and other phytochemicals in corn (Chander et al 2008;Mahan et al 2013) than environment and genotype by environment interaction. The results indicated that selection for individual characters would be possible as sample variations are available for these characters.…”
Section: Discussionmentioning
confidence: 99%
“…When low interaction effects were considered, MAC, DPPH, and TEAC were rather stable and might be useful as selection criteria for improvement of corn genotypes with high antioxidant capacity. The low interactions of genotype 9 environment are preferable, indicating that the relative performance in one season is reliable in predicting relative performance in another season (Knievel et al 2009;Hasting et al 2012;Mahan et al 2013). With low G 9 E interaction and little error variance, the relative performance across seasons or environment should be similar.…”
Section: Discussionmentioning
confidence: 99%
“…First is a collection of 479 samples (Set 1) resulting from 84 hybrids tested in three locations with two replicates as described by Mahan et al (2013) that served as the basis of the initial calibrations as well as for choosing breeding samples to expand the calibration. First is a collection of 479 samples (Set 1) resulting from 84 hybrids tested in three locations with two replicates as described by Mahan et al (2013) that served as the basis of the initial calibrations as well as for choosing breeding samples to expand the calibration.…”
Section: Plant Materialsmentioning
confidence: 99%
“…These samples were analyzed by HPLC to determine the specific anthocyanin compounds Figure 3. It was determined that these samples primarily contained more malonated anthocyanins (especially Cyanidin-3-(6-malonylglucoside) = 54.79 cyanidin equivalents mg/g, db; pelargonidin-3-malonyl glucoside = 10.67 pelargonidin equivalents, mg/g, db; and peonidin-3-malonyl glucoside = 15.74 cyanidin equivalents, mg/g, db) than others in their color class or any of 47 hybrid samples investigated (Collison, 2013), which were mostly derived from sample Set 1 (Mahan et al, 2013). and concentrations contributing to their EPC and color ( Supplementary Fig.…”
Section: Identification Of Color Compounds In the Highest Extractablementioning
confidence: 99%